Meditasi Kristiani: Solusi Pemulihan Mental health dan Peningkatan Spiritualitas Generasi Z di Era Digital - Aprilia, Debora; Sirait, Hikman; Meriyana, Meriyana (Sekolah Tinggi Teologi Kanaan Nusantara, 2025)
This research discusses Christian meditation as a solution for Gen Z's mental health and spirituality enhancement in the digital age. In Christian circles, meditation is often viewed negatively as it is thought to be associated with mystical practices or New Age groups. However, Christian meditation, which has its roots in Jewish tradition, aims to establish communication with God through contemplation of the Bible. Gen Z, who are prone to mental disorders and spiritual crises, face challenges in the digital age. This study aims to reveal how Christian meditation can help improve their mental health and deepen their spirituality. The method used is a qualitative approach with literature analysis and case studies related to Christian meditation, mental health, and the development of Gen Z's spirituality. It can be concluded that digital technology has a significant impact on Gen Z's mental health, including increased anxiety, stress, and decreased quality of life. In the face of such pressures, Christian meditation, offers a spiritual solution that fosters inner peace and a deeper connection with God. Therefore, churches and Christian communities need to integrate Christian meditation as a means of mental recovery and strengthening Gen Z's spirituality in the digital age.AbstrakGenerasi Z menghadapi tantangan serius dalam kesehatan mental dan spiritualitas di era digital, termasuk meningkatnya kecemasan, stres, dan krisis identitas rohani. Di sisi lain, meditasi Kristiani sering dipandang negatif karena dianggap berkaitan dengan praktik mistis atau gerakan New Age. Padahal, meditasi Kristiani berakar dari tradisi Yahudi dan bertujuan membangun relasi dengan Allah melalui perenungan Kitab Suci. Metode yang digunakan adalah pendekatan kualitatif dengan analisis literatur dan studi kasus terkait meditasi Kristen, kesehatan mental, serta perkembangan spiritualitas Gen Z. Maka dapat disimpulkan bahwa teknologi digital memberikan dampak signifikan terhadap kesehatan mental Gen Z, termasuk meningkatnya kecemasan, stres, dan penurunan kualitas hidup. Dalam menghadapi tekanan tersebut, meditasi Kristen, menawarkan solusi rohani yang menumbuhkan kedamaian batin dan hubungan yang lebih dalam dengan Tuhan. Oleh karena itu, gereja dan komunitas Kristen perlu mengintegrasikan meditasi Kristiani sebagai sarana pemulihan mental dan penguatan spiritualitas Gen Z di era digital.